2023
DOI: 10.1038/s41467-023-36564-3
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic oscillation controls multidecadal changes in the North Tropical Atlantic−Pacific connection

Abstract: By exciting subtropical teleconnections, sea surface temperature (SST) anomalies in the North Tropical Atlantic (NTA) during boreal spring can trigger El Niño-Southern Oscillation (ENSO) events in the following boreal winter, thereby providing a precursor for ENSO predictability. However, this NTA−ENSO connection is not stationary, and it varies considerably over multidecadal timescales, which cannot be directly explained by the Atlantic multidecadal oscillation or the global warming trend. Here we show that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…The abovementioned study, similar to Ding et al (2023), attributes the NTA effect on ENSO in CMIP5 and CMIP6 models to the spring climatological mean Atlantic ITCZ precipitation and spring-to-summer NTA SST persistence. Moreover, Discussions regarding reasons affecting the NTA-ENSO connection in CMIP models are ongoing.…”
Section: Summary and Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The abovementioned study, similar to Ding et al (2023), attributes the NTA effect on ENSO in CMIP5 and CMIP6 models to the spring climatological mean Atlantic ITCZ precipitation and spring-to-summer NTA SST persistence. Moreover, Discussions regarding reasons affecting the NTA-ENSO connection in CMIP models are ongoing.…”
Section: Summary and Discussionmentioning
confidence: 77%
“…Besides, Park et al (2022) found that the strength of the NTA effect on ENSO in the CMIP5 models tended to correlate positively with the intensity of the boreal spring climatological subtropical North Pacific high system. More recently, Ding et al (2023) used observational data to show that during the positive phase of the NAO, the amplification of the NTA impact on ENSO is due mainly to the strengthening of the spring climatological mean Atlantic ITCZ precipitation and NTA SSTAs persistence, which increases enhance the NTA influence by exciting stronger and more persistent subtropical teleconnections. Motivated by this fact, we turn to the state-of-the-art CMIP climate models in addition to observations.…”
mentioning
confidence: 99%
“…So, these previous studies imply that the atmospheric variations over the mid-high latitude (AO/NAO-like) appear to modulate the NTA-ENSO connection Chen et al, 2018;Ding et al, 2023). In particular, the NAOlike atmospheric anomalies tend to depict an atmosphere-toocean forcing to the central tropical Pacific SST anomalies through the NTA SST anomalies (Wu, 2010;Karnauskas, 2014;Ding et al, 2017;Ding et al, 2023). As NAO-like footprints of the 11-year solar cycle are found in previous studies (Thiéblemont et al, 2015;Drews et al, 2022;Kuroda et al, 2022), we assume that the basin connection between NTA and tropical Pacific may provide a possible indirect route for the 11-year solar cycle impact on the tropical Pacific SST.…”
Section: Introductionmentioning
confidence: 85%
“…This could be due to the internal variability in the North Pacific (Chen et al, 2022) and the model's ability in reproducing spring Arctic Oscillation (AO)-associated atmospheric anomalies over the subtropical North Pacific (Zheng et al, 2021). So, these previous studies imply that the atmospheric variations over the mid-high latitude (AO/NAO-like) appear to modulate the NTA-ENSO connection Chen et al, 2018;Ding et al, 2023). In particular, the NAOlike atmospheric anomalies tend to depict an atmosphere-toocean forcing to the central tropical Pacific SST anomalies through the NTA SST anomalies (Wu, 2010;Karnauskas, 2014;Ding et al, 2017;Ding et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation